Legibility of Web Page on Full High Definition Display - Ahmad Affendi, Hashim; Mazlina, Abdul Majid; Balsam, A. Mustafa (2013)
This paper explored the impact of legibility on full high definition (Full-HD) liquid crystal display (LCD) for video display terminal (VDT). A total of 117 participants were tested for legibility of 13 colour combinations based on more than 90-year-old Le Courier Table of Legibility. The participants first completed a survey online, then they were presented to a text designed using Wilkins Rate of Reading Test. The text is seeded with spelling errors in some of the words. The Participants then counted the number of words that have spelling errors, and recorded it to measure the legibility of the colour combinations.The results proved that Le Courier table of legibility is not suitable with the Full-HD LCD.